2012
DOI: 10.1089/lap.2011.0376
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adrenalectomy: Lessons Learned from 306 Cases

Abstract: Introduction: Laparoscopic adrenalectomy has become the standard of care for the surgical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…It is a benign tumour in the adrenal cortex composed of mixture of adipose tissue and bone marrow (haematopoietic) elements. In large series, adrenal myelolipoma comprises approximately 3-4% of primary adrenal tumour (Lam & Lo 2001, Kulis et al 2012, Shenoy et al 2015.…”
Section: Myelolipomamentioning
confidence: 99%
“…It is a benign tumour in the adrenal cortex composed of mixture of adipose tissue and bone marrow (haematopoietic) elements. In large series, adrenal myelolipoma comprises approximately 3-4% of primary adrenal tumour (Lam & Lo 2001, Kulis et al 2012, Shenoy et al 2015.…”
Section: Myelolipomamentioning
confidence: 99%
“…Kulis et al [19] published his series of 306 patients using the transperitoneal lateral approach for LA. No major operative complications were noted, and postoperative complications included a pulmonary embolism and two cases of pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…The median hospitalization was 4±3.7 days (range, 2-22 days). Adrenal pathology included adenoma (n=164), pheochromocytoma (n=79), hyperplasia (n=35), metastatic carcinoma (n=22), cyst (n=9), myelolipoma (n=9), hemangioma (n=3), ganglioneuroma (n=3), and melanoma (n=2) [19].…”
Section: Resultsmentioning
confidence: 99%
“…Open adrenalectomy has been mostly replaced by LA for over a decade. Numerous studies have demonstrated the safety and efficacy of LA in different approaches [4,8]. At present, no clear advantage between the transperitoneal and retroperitoneal approaches has been shown [9].…”
Section: Discussionmentioning
confidence: 99%
“…LA has become the operative procedure of choice for most adrenal tumors [2]. Many studies have reported the efficacy and safety of LA [3,4]. The small size of adrenal glands, located in the retroperitoneal space surrounded by major intraabdominal organs and great vessels, makes LA an ideal approach.…”
mentioning
confidence: 99%